The light against the darkness: The first confrontations between the Church and Freemasonry in Uruguay, Argentina and Chile (1857-1860) - del Solar, Felipe Santiago (2022)
This paper analyzes from a transnational perspective the beginning of the conflict between the Catholic Church and Freemasonry in Uruguay, Argentina and Chile. The research hypothesis states that the debate in the public sphere allowed Freemasonry to be endowed with a secular and liberal identity that favored its growth and consolidation in the region; and the Church, for its part, was allowed to rehearse a strategy of regional resistance directed from Rome that it will later implement against the processes of secularization of the nation states.